Sporophytic self-incompatibility in Senecio squalidus (Asteraceae): S allele dominance interactions and modifiers of cross-compatibility and selfing rates. - Brennan, A; Tabah, D; Harris, S; Hiscock, S (2011)
Understanding genetic mechanisms of self-incompatibility (SI) and how they evolve is central to understanding the mating behaviour of most outbreeding angiosperms. Sporophytic SI (SSI) is controlled by a single multi-allelic locus, S, which is expressed in the diploid (sporophyte) plant to determine the SI phenotype of its haploid (gametophyte) pollen. This allows complex patterns of independent S allele dominance interactions in male (pollen) and female (pistil) reproductive tissues. Senecio squalidus is a useful model for studying the genetic regulation and evolution of SSI because of its population history as an alien invasive species in the UK. S. squalidus maintains a small number of S alleles (7-11) with a high frequency of dominance interactions. Some S. squalidus individuals also show partial selfing and/or greater levels of cross-compatibility than expected under SSI. We previously speculated that these might be adaptations to invasiveness. Here we describe a detailed characterization of the regulation of SSI in S. squalidus. Controlled crosses were used to determine the S allele dominance hierarchy of six S alleles and effects of modifiers on cross-compatibility and partial selfing. Complex dominance interactions among S alleles were found with at least three levels of dominance and tissue-specific codominance. Evidence for S gene modifiers that increase selfing and/or cross-compatibility was also found. These empirical findings are discussed in the context of theoretical predictions for maintenance of S allele dominance interactions, and the role of modifier loci in the evolution of SI.